The solbot / Syed Ali Syed Mat Zain, Tuan Mohammad Zaidi Tuan A Talib and Wan Muhammad Akram Wan Mohd Salizam - Syed Mat Zain, Syed Ali; Tuan A Talib, Tuan Mohammad Zaidi; Wan Mohd Salizam, Wan Muhammad Akram (2010)
This project is about a static robot alive with can make a movement such as movement on arm, head , and can also show some greeting display on their chest such as “Good Morning” or “Welcome to Our Faculty of Electrical Engineering” . This project, codename ‘SOLBOT’ are designed and used the recycled material that commonly not used anymore such as mineral plastic bottle, some iron or metal and others. This project can be widely used in many situations for represent an alive landmark or mascot or commercial purpose. The interesting part of this project is this SOLBOT are made from recycled material and also used solar as energy source by means we can save a lot of garbage and energy and also can solve our global warming by recycle back useless material.